The interface of language, vision, and action : eye movements and the visual world - Henderson, John M. (John Michael), 1958-; Ferreira, Fernanda, 1960- (Psychology Press, 2004)
This book explores common theoretical issues, empirical findings, technical problems, and outstanding questions and will serve as a blueprint for work on the interface of vision, language, and action over the next five to ten years.